Spectral management in upconverting sesquioxide through matrix doping. Issue 38 (7th September 2015) - Xu, Dekang; Lin, Hao; Li, Anming; Yang, Shenghong; Zhang, Yueli
Abstract : Simultaneous upconversion luminescence intensity and color tuning in Gd2 O3 :Yb/Er through matrix doping with GdOF. Abstract : Designing luminescent materials with tunable emission has always been a frontier topic of color display, photovoltaic and biodetection technologies. Despite their excellent modulation between the material composition/phase/morphology/preparation and performance, an efficient route is desired to simultaneously tune the emission color and intensity. Herein, we demonstrate the simultaneous spectral tuning in the Gd2 O3 host by matrix doping using a fast and facile hydrothermal method by simply adding a fluoride source during the preparation of gadolinium-based precursors. Structural and optical microscopic characterization shows that GdOF is homogeneously incorporated into Gd2 O3 micro-sized rod-like particles. Our mechanistic investigations of upconversion luminescence behaviors suggest that the spectral tunability of this structure is governed by the dominant energy transfer upconversion for the depletion of the intermediate manifolds and the reduced probabilities of multiphonon relaxation and energy back transfer processes, which results from the decreasing effective phonon energy, the refractive index and the average Ln 3+ distance by doping GdOF. These findings provide useful information on designing and developing luminescent materials within simple structures for efficient spectral tuning, which may be found suitable for photovoltaic, display devices and security techniques.